Effectiveness of Vetiver System for the Treatment of Wastewater from an Institutional Kitchen. (2016) - Mathew, Mini; Rosary, Sr. Claramma; Sebastian, Mathukutty; Cherian, Sandra Maria
Abstract: This paper investigates the potential of using Vetiver System (VS) for the treatment of wastewater generated from an Institutional kitchen. Vetiver grass is a perennial grass with deep root and has high biomass system. Researchers proved that Vetiver grass have extraordinary ability to with stand extreme environmental conditions such as elevated levels of salt, acidity, alkalinity, sodicity as well as whole range of heavy metals, nitrogen (N), and phosphorous (P). There are around 800 inmates in this institutional hostel; as a result large amount of wastewater have been produced everyday in campus kitchen wastewater outlet. A pilot experimental setup was made for the treatment of wastewater produced from the wastewater outlet and the capability of using VS for the treatment was studied. Experimental setup includes 5 drums of130 liters capacity and is filled with soil, the Vetiver grass is planted in them and was connected in series using different pipe fittings. Each tank has outlet at the bottom of the tank and inlet provided at top with sufficient free board. The wastewater was supplied through the inlet of the 1 st tank and was allowed to pass through the 2 nd, 3 rd, 4 th and 5 th tanks and the treated water was collected at the outlet of the 5 th tank. The water quality parameters of wastewater and treated water were analysed and the effectiveness of using VS for the treatment was assessed. The various water quality parameters like pH, turbidity, acidity, alkalinity, BOD, COD, DO, Ecoli were analysed for the wastewater and treated water. It is observed that the wastewater treatment using VS has significant potential to reclaim the wastewater. The VS is able to remove 80 to 85% of BOD, 85 to 90% of COD, and 85% of total Coliform. Most of the water quality parameters are within permissible limits as per IS 10550, 2012 and IS 2292, 1992.